Sampling Design Influences the Observed Dominance of Culex tritaeniorhynchus: Considerations for Future Studies of Japanese Encephalitis Virus Transmission. - Jennifer S Lord; Hasan Mohammad Al-Amin; Sumit Chakma; Mohammad Shafiul Alam; Emily S Gurley; Juliet R C Pulliam (Public Library of Science (PLoS), 2016)
Mosquito sampling during Japanese encephalitis virus (JEV)-associated studies, particularly in India, has usually been conducted via aspirators or light traps to catch mosquitoes around cattle, which are dead-end hosts for JEV. High numbers of Culex tritaeniorhynchus, relative to other species, have often been caught during these studies. Less frequently, studies have involved sampling outdoor resting mosquitoes. We aimed to compare the relative abundance of mosquito species between these two previously used mosquito sampling methods. From September to December 2013 entomological surveys were undertaken in eight villages in a Japanese encephalitis (JE) endemic area of Bangladesh. Light traps were used to collect active mosquitoes in households, and resting boxes and a Bina Pani Das hop cage were used near oviposition sites to collect resting mosquitoes. Numbers of humans and domestic animals present in households where light traps were set were recorded. In five villages Cx. tritaeniorhynchus was more likely to be selected from light trap samples near hosts than resting collection samples near oviposition sites, according to log odds ratio tests. The opposite was true for Cx. pseudovishnui and Armigeres subalbatus, which can also transmit JEV. Culex tritaeniorhynchus constituted 59% of the mosquitoes sampled from households with cattle, 28% from households without cattle and 17% in resting collections. In contrast Cx. pseudovishnui constituted 5.4% of the sample from households with cattle, 16% from households with no cattle and 27% from resting collections, while Ar. subalbatus constituted 0.15%, 0.38%, and 8.4% of these samples respectively. These observations may be due to differences in timing of biting activity, host preference and host-seeking strategy rather than differences in population density. We suggest that future studies aiming to implicate vector species in transmission of JEV should consider focusing catches around hosts able to transmit JEV.